Cost–utility analysis of prophylaxis versus treatment on demand in severe hemophilia A - Maria Elisa Mancuso; Sergio Di Matteo; Giorgio L Colombo; et al (Dove Medical Press, 2011)
Giorgio L Colombo1,2, Sergio Di Matteo2, Maria Elisa Mancuso3, Elena Santagostino31University of Pavia, School of Pharmacy, Pavia, Italy; 2S.A.V.E. Studi Analisi Valutazioni Economiche, Milan, Italy; 3Angelo Bianchi Bonomi Hemophilia and Thrombosis Center, Fondazione IRCCS Ca' Granda, Ospedale Maggiore Policlinico, Milan, ItalyBackground: Individuals with severe hemophilia A have reduced blood levels of clotting factor VIII (FVIII) leading to recurrent bleeding into joints and muscles. Primary prophylaxis with clotting factor concentrates started early in childhood prevents joint bleeds, thus avoiding joint damage and improving people's quality of life. There remain significant differences in the implementation of primary prophylaxis worldwide mainly due to the cost of prophylaxis compared with treatment on demand.Objective: To evaluate the cost-effectiveness of primary prophylaxis with FVIII concentrates versus secondary prophylaxis, versus treatment on demand, and versus a "hybrid" (primary prophylaxis followed by on-demand treatment in adults) in individuals with severe hemophilia A.Methods: A Markov model was developed and run using different sources of clinical, cost, and utility data. The model was populated with a hypothetical cohort of 100 individuals with severe hemophilia A. The perspective of the Italian National Health System was used.Results: The baseline results showed that primary and secondary prophylaxis is cost-effective compared both with treatment on demand and with a hybrid strategy. The incremental costs per quality-adjusted life-year gained for individuals with hemophilia A receiving primary and secondary prophylaxis were €40,229 to €40,236 versus an on-demand strategy. However, the sensitivity analyses performed showed that the results were sensitive to the unit cost of clotting FVIII, bleeding frequency, and the discount rate.Conclusion: Although primary prophylaxis is a costly treatment, our results show that it is cost-effective compared with treatment on demand.Keywords: hemophilia, cost-utility, factor VIII, prophylaxis, treatment on demand, quality of life